Odpowiedzi

2009-10-27T10:56:53+01:00
A) (a-4)(a+5)=akwadrat+5a-4a-20=a kwadrat+a-20
b) (7b+3)(2-4b)=-28bkwadrat+14b+6-12b=-28bkwadrat+2b+6
c) (-3c+2d)(2c-6)=-6ckwadrat+18c+4dc-12d=-2(3ckwadrat-9c-2dc+6d)
d) (9s-2t)(7t-s)=63st-9skwadrat-14tkwadrat+2ts=65st-9skwadrat-14tkwadrat
e) (-10m+3n)(5n-4)=-50m*n+40m+15nkwadrat-12n
f) (3kl+8k)(4-2l)=12kl-6kl kwadrat+32k-16kl=-4kl-6klkwadrat+32k
g) (4xy+3x)(2y+5x kwadrat y)=4xykwadrat+20xdo trzeciej*(ykwadrat)+6xy+15x(do trzeciej)y
4 5 4
2009-10-27T10:57:46+01:00
Mnożymy każdy wyraz z każdym
a) (a-4)(a+5) = a²+5a - 4a -20 = a² +a -20

b) (7b+3)(2-4b)= 14b - 28b² +6 -12b = -28b² +2b +6

c) (-3c+2d)(2c-6)= -6c²+18c +4cd -12d

d) (9s-2t)(7t-s)= 63st - 9s² - 14 t² +2st = -61st- 9s² - 14 t²

e) (-10m+3n)(5n-4)= -50mn+40m +15n² -12n

f) (3kl+8k)(4-2l)=12kl -6kl² + 32k - 16kl = -4kl-6kl² + 32k

g) (4xy+3x)(2y+5xy²)=8xy²+20x²y³+6xy+15x²y²

h) (-2p²q-3p)(5pq-3p²-q²) = -10p³q²+6p⁴q+2p²q³-15p²q+9p³+3pq²
4 5 4
  • Użytkownik Zadane
2009-10-27T11:01:46+01:00
A) (a-4)(a+5)=a²+a-20²


b) (7b+3)(2-4b)= 14b - 28b² +6 -12b = -28b² +2b +6

c) (-3c+2d)(2c-6)= -6c²+18c +4cd -12d

d) (9s-2t)(7t-s)= 63st - 9s² - 14 t² +2st = -61st- 9s² - 14 t²

e) (-10m+3n)(5n-4)= -50mn+40m +15n² -12n

f) (3kl+8k)(4-2l)=12kl -6kl² + 32k - 16kl = -4kl-6kl² + 32k

g) (4xy+3x)(2y+5xy²)=8xy²+20x²y³+6xy+15x²y²

h) (-2p²q-3p)(5pq-3p²-q²) = -10p³q²+6p⁴q+2p²q³-15p²q+9p³+3pq²
4 5 4